Recovery of Olfactory Function Induces Neuroplasticity Effects in Patients with Smell Loss - Kathrin Kollndorfer; Ksenia Kowalczyk; Elisabeth Hoche; Christian A. Mueller; Michael Pollak; Siegfried Trattnig; Veronika Schöpf (Neural Plasticity)
The plasticity of brain function, especially reorganization after stroke or sensory loss, has been investigated extensively. Based upon its special characteristics, the olfactory system allows the investigation of functional networks in patients with smell loss, as it holds the unique ability to be activated by the sensorimotor act of sniffing, without the presentation of an odor. In the present study, subjects with chronic peripheral smell loss and healthy controls were investigated using functional magnetic resonance imaging (fMRI) to compare functional networks in one of the major olfactory areas before and after an olfactory training program. Data analysis revealed that olfactory training induced alterations in functional connectivity networks. Thus, olfactory training is capable of inducing neural reorganization processes. Furthermore, these findings provide evidence for the underlying neural mechanisms of olfactory training.